You and I : living and learning. Learning another Language - Newfoundland and Labrador Association for Adult Education (Memorial University of Newfoundland. Educational Television Centre, 1982)
In this episode host Bill Shallow speaks with Mary Selman and Judith Mastai, experts in teaching English as a second language about teaching this subject in Newfoundland and Labrador, as well as teaching any language as a second language.